Endothelial function, insulin sensitivity and inflammatory markers in hyperprolactinemic pre-menopausal women - YAVUZ, DİLEK; HAKLAR, GONCAGÜL; GÖZÜ, HÜLYA (BIOSCIENTIFICA LTD, 2003)
Background: Hyperprolactinemia has been reported to be associated with abnormalities of carbohydrate metabolism. The aim of this study was to evaluate the effects of hyperprolactinemia and bromocriptine (Brc) treatment on endothelial function, insulin sensitivity and inflammatory markers in pre-menopausal women. Methods: Sixteen hyperprolactinemic pre-menopausal women with pituitary adenomas were recruited and 20 healthy subjects were included as controls. Patients were given Brc in doses of 2.5-20 mg/dl until normal levels of prolactin were reached. Prior to treatment and 2 months after prolactin levels were normalized, the following tests were performed. Insulin sensitivity was determined by an oral glucose tolerance test based on a formula named the insulin sensitivity index (ISI composite). Endothelial function was measured as flow-mediated dilatation (FMD) on a brachial artery using high resolution ultrasound. Results: Serum glucose, insulin, estrogen, highly sensitive C-reactive protein (hsCRP), fibrinogen, homocysteine and uric acid levels were measured. Calculated ISI composite and FMD were significantly lower in the hyperprolactinemic group in comparison with the controls and improved after Brc treatment. Serum homocysteine, hsCRP and uric acid levels were significantly higher in hyperprolactinemic patients than in the controls and returned to normal levels with Brc treatment. Serum prolactin concentrations were inversely correlated with FMD measurements (r = - 0.68; P < 0.0001), ISI composite (r = - 0.48; P < 0.005) and serum estrogen (r = - 0.54; P < 0.005), and positively correlated with serum homocysteine concentrations (r = 0.55; P < 0.0001) in the hyperprolactinemic group. Conclusions: The hyperprolactinemic state is associated with impaired endothelial function and decreased insulin sensitivity, which are early markers of atherosclerosis. These alterations may predispose to the development of atherosclerosis in non-treated cases. Correction of the hyperprolactinemic state is associated with improved endothelial function and insulin sensitivity.
Keywords: REACTIVE PROTEIN-LEVELS; HOMOCYSTEINE LEVELS; GLUCOSE-TOLERANCE; PANCREATIC-ISLETS; RESISTANCE; ATHEROSCLEROSIS; DYSFUNCTION; PROLACTIN; DISEASE; HYPERHOMOCYSTEINEMIA